Analyzing the Effects of Visual and Verbal Stimuli in Students’ Production of Written Narratives - Dr. Sirhajwan Idek, Nur Syuhadah Aieza, Ryan derrick Siggoh, Ibrahim Ismail, Mary Gorette Valintine, (International Journal of Advanced Science and Technology, 2020)
The aim of this research was to investigate the effects of two types of stimuli, visual and verbal stimuli, in triggering students’ interpretations and expressions of these interpretation in English language which was their second language. The subjects were 40 secondary school students whose English proficiency was limited and therefore classified as novice learners. These students were from a vocational school located in the interior region of the island state, Sabah, Malaysia. They tended to merely recite and rewrite their answers to textual prompts which did little in improving their skills in producing ideas of their own in their own words. In this research, the students were presented with a list of vocabulary (verbal stimulus) and a still image (visual stimulus) and they were required to write a short narrative based on these two types of stimuli. Their responses were analyzed through holistic rubric which encompassed image, characterization, voice and story. The findings showed that the written responses produced by the students towards visual stimulus contained richer imagination, stronger plot and complex sentences than the written responses produced towards verbal stimuli. This suggested that visuals might be more effective in encouraging students to explore and express their creativity in the target language by using their own words.